Family-concentrated ownership in Chinese PLCs: Does ownership concentration always enhance corporate value? - Jin-hui Luo; Heng Liu (International Journal of Financial Studies, 2014)
In this paper we investigate the relationship between family ownership structure and corporate value across a sample of 1314 firm-year observations of China's family publicly listed companies (PLCs), from 2004 to 2008. We find a significant inverse-U-shaped relationship between the controlling family's ultimate cash-flow rights and corporate value; as measured by Tobin's Q. That is, as family-ownership concentration increases, corporate value first increases and then decreases. This finding refreshes our understanding of the relationship between family-ownership concentration and corporate value in emerging economies such as found in China. We corroborate prior findings that when controlling families hold excess control over cash-flow rights, corporate value is significantly lowered, while multiple large shareholders structure is significantly associated with higher corporate value. In addition; board independence is found to significantly improve corporate value in the context of family-concentrated ownership. We also test for potential endogeneity between family ownership and corporate value and find our results to be robust.
Keywords: 330; China; corporate value; family concentrated ownership; family firms; ultimate ownership structure